Advocating for Service-Learning as a pedagogical model in Physical Education: towards an activist and transformative approach. (3rd September 2022) - Chiva-Bartoll, Oscar; Fernández-Rio, Javier
ABSTRACT: Background: There seems to be a need to rethink education and shape the future to build more equitable societies. In line with this idea, Service-Learning (SL) has emerged as an educational approach to integrate curricular learning and the provision of a community service. Unfortunately, many SL implementations in Physical Education lack a concrete frame of reference to guide them. Purpose: Using the model-based practice framework, this paper aims to make the case to consider SL a pedagogical model to put transformative and socially critical Physical Education discourses into operation in real contexts. Method: The article is structured around two main parts. Part 1 includes the criteria that any advocacy for a model should present within the models-based practice framework. Part 2 is divided into different subsections to introduce the theoretical foundations of SL, the major theme, the teaching implications and learning aspirations, exemplification of a particular case, and critical elements and benchmarks. It also contains a review of the research findings and reference networks and organizations that, despite not seeing SL specifically as a pedagogical model, report its development in Physical Education around the world. Results and implications: In addition to setting the general bases and criteria to make the case for a pedagogical model, the paper addresses the main instructional implications for Physical Education: learning outcomes and teaching strategies. The work suggests that by considering the experiential, critical and transformative principles of the model, its major learning impact is upon the affective and social domains, in connection with the major theme identified: 'learning by serving'. Another relevant contribution of the article is that it provides implementation guidelines through a 10-item checklist with benchmarks that typify SL's key features. This checklist could be of value, since it can help practitioners and researchers to describe and verify future implementations. Conclusion: SL has the necessary elements to be considered an activist, transformative, trans-domain and inter-contextual pedagogical model in Physical Education. Its dual major theme (learning by serving) uncovers new perspectives on teaching and learning in Physical Education, promoting the students' social and affective domains. SL provides a connection between learning, teaching, content and context, requiring teachers and students to develop a commitment to the underlying philosophy of the model. Moreover, it occupies alternative spaces and locations to those traditionally used in Physical Education, and it can help develop genuine relationships between educators and students from schools and individuals and organizations from the community.